Probing the Folding of Peptide–Polymer Conjugates Using the π-Dimerization of Viologen End-Groups - Otter, Ronja; Besenius, Pol (Organic Materials, 2020)
The synthesis of a foldable viologen-functionalized peptide–polymer conjugate is presented. The ABA-type triblock conjugate with a PEG polymer was capped with a FHFHF pentapeptide sequence and further modified with a viologen building block at both chain ends. The pH-responsive peptide domains fold into an intermediate structure inducing close proximity of the viologen units, which upon a reduction step form π-dimers of the radical cation. Overall the intramolecular folding and intermolecular self-assembly process leads to the formation of supramolecular nanorods. Mixing of viologen-peptide–polymer conjugates with unfunctionalized conjugates leads to crosslinking of the nanorods and hydrogels with a tunable content of viologen end groups. π-Dimerization in the gels induces a deep purple color, which is used as an optical probe to monitor the diffusion of molecular oxygen through the hydrogel matrix.
Keywords: supramolecular materials; stimuli-responsive polymers; electrochromism; peptide conjugation; hydrogel